2018
DOI: 10.1002/jpln.201800337
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic phytotoxicity and accumulation in rice seedlings grown in arsenic‐contaminated soils as influenced by the characteristics of organic matter amendments and soils

Abstract: Organic matter (OM) application into soils is a common agricultural practice. Previous studies have shown that in arsenic (As)‐contaminated paddy soils, OM has the potential to alter the behavior of As and affects the growth and As accumulation of rice plants. In this study, pot experiments were conducted to investigate the differences in the amounts of As released into soil solutions, its toxicity, and accumulation in rice seedlings caused by application of three different OM amendments [soybean meal (SB), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…OM in soil may influence the mobility and bioavailability of As over redox reactions, anions (phosphate, DOC and silicate), As-OM complexation and competitive adsorption [81]. OM may also affect plant growth and As accumulation in rice plants.…”
Section: Soil Organic Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…OM in soil may influence the mobility and bioavailability of As over redox reactions, anions (phosphate, DOC and silicate), As-OM complexation and competitive adsorption [81]. OM may also affect plant growth and As accumulation in rice plants.…”
Section: Soil Organic Mattermentioning
confidence: 99%
“…Norton et al [83] stated that OM is important in the mobilisation of As from paddy fields because microbes utilising OM consume oxygen that results in a reduction in redox potential, which leads to As dissolution from FeOOH. Syu et al [81] explained that the characteristics of soils and OMs should be considered before using OM amendments to As-polluted soils. The use of OM to As-polluted soils may exert different effects on the As accumulation and growth of rice plants [81].…”
Section: Soil Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, iron oxides are the predominant arsenic adsorbents in hydromorphic soils/paddy soils (Vithanage et al, 2013;Zhu et al, 2019). The two manures used were abundant in organic matter, generating dissolved organic carbon into the soils, which desorbs more arsenic in soils rich in indigenous iron oxides binding arsenic and increases mobile arsenic in soil solutions for plant uptake (Syu et al, 2019;Williams et al, 2011). Also, soils with high pH are commonly low in arsenic retention capability (Syu et al, 2019;Wang et al, 2015), which facilitates arsenic assimilation 325 in rice plants.…”
Section: Effect Of Soil Properties On Arsenic Uptake By Rice Plantmentioning
confidence: 99%
“…Thus, the elucidating the bio-decomposability of each OAM is crucial for determining their relative As dissolution potential in anaerobic soils with OAMs, although the actual amount or rate of As dissolution is dependent on the soil properties and total As contents. Nonetheless, most studies on As dissolution in soils with OAMs have not presented detailed OAM properties, and only few studies have focused on their bio-decomposability and As dissolution in applied soils 25,26 . The carbon to nitrogen ratio (C/N) has been frequently considered a factor affecting the bio-decomposability of OAMs [27][28][29] : for instance, Suda and Makino 25 demonstrated that the application of OAMs with low C/N led to a rapid decrease in soil redox potential (i.e., rapid decomposition, and thereby accelerated As dissolution from anaerobic soils).…”
mentioning
confidence: 99%